Eficacia de la utilización del software Compers en el subproceso de evaluación de desempeño en 360 grados - Benavides Leiva, David Alejandro (2009)
The Compers software is one of the technological tools that allows the development of the human talent area of the organization. This method allows to automate all the subprocesses that encompasses Human Resources Management regardless of the type of entity that belongs to the market. The interaction with new technology allows employees to have updated knowledge and be prepared to grow professionally in the business field. This research work aims to propose new resources to improve the work of the Human Talent Department, therefore the results show that Compers software can be one of the most appropriate technological tools to get involved with the administration of internal staff any company ...